Determination of Product Orders Based on the Analytical Hierarchy Process Method - Kurnia, Dona (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
Decision-making in determining product orders is a method that managers can use to determine the type of product to be ordered again based on previous sales. Product orders to be reordered will be determined based on the highest number of sales among similar products. One of the methods that can be used is the AHP method, where the AHP method can assist managers in making decisions by providing a sequence of decision alternatives accompanied by a percentage on each alternative. The research method used in this journal is the system development life cycle (SDLC) which can describe the activities in this research in detail. The application of product orders with the AHP method will be applied to a case, namely an order for clothing products at a well-known clothing outlet in Bukittinggi. The product order system will be implemented into an application designed with the Visual Basic 2010 programming language and MySQL database to make it easier for managers to make decisions. With this research, it is hoped that it can help store managers in making decisions for determining clothing orders so that they can produce the best decisions that can provide benefits in the business that is being undertaken.